Trends in Nanophysics Theory, Experiment and Technology - Aldea, Alexandru; Bârsan, Victor (Engineering Materials,, 2010)
"Trends in Nanophysics" contains reviews on various domains of nanotechnology such as: radiation-induced polymerization, cross-linking and grafting; Mossbauer study of nanomaterials; biomedical applications of nanomaterials; organic thin films for photovoltaics; growth and characterization of semiconductor nanowires; graphene and carbon nanotubes; fractional statistics in nanophysics; nanomechanical properties of materials; ab-initio simulations in nanoscience; fabrication and characterization of ordered atomic-scale structures; plasmonics; and nano-optical studies of motile structures of neuronal cells. These reviews cover key issues from experimental and theoretical nanophysics and are interesting for active researchers as well as for graduate and undergraduate students in the nanoscience field.